2013
DOI: 10.1097/brs.0b013e31827ecbf1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cranial Facet Joint Violation Rates Between Open and Percutaneous Pedicle Screw Placement Using Intraoperative 3-D CT (O-arm) Computer Navigation

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 27 publications
1
65
0
1
Order By: Relevance
“…Therefore, pedicle screw fixation and lamina posterolateral bone graft fusion during operation are not reliable for the stability maintenance of the integral spinal column, namely that strengthening the stability of the posterior column merely has no noticeable effect on the stability of the anterior and central columns. Plain CT scanning images of the fracture at the long-term follow-up show that the empty intravertebral cavity is always present (19,20). As vertebral stability is mainly involved in the anterior middle spine (accounting for ∼60%), performing posterolateral fusion during surgery is not reliable and is ineffective for the stabilization of the anterior middle spine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pedicle screw fixation and lamina posterolateral bone graft fusion during operation are not reliable for the stability maintenance of the integral spinal column, namely that strengthening the stability of the posterior column merely has no noticeable effect on the stability of the anterior and central columns. Plain CT scanning images of the fracture at the long-term follow-up show that the empty intravertebral cavity is always present (19,20). As vertebral stability is mainly involved in the anterior middle spine (accounting for ∼60%), performing posterolateral fusion during surgery is not reliable and is ineffective for the stabilization of the anterior middle spine.…”
Section: Discussionmentioning
confidence: 99%
“…26 This may be related to the fact that an accurate intraoperative CT scan may allow the surgeon to project the virtual screw trajectory in all 3 planes and adjust the entry point and direction based on pseudo-real-time feedback. However, another study on patients undergoing TLIF did not find a similar benefit with the use of O-arm navigation.…”
Section: 6mentioning
confidence: 99%
“…Even with perfect fluoroscopic images, a slightly poor choice of entry site or too much medial angulations can result in a violation. A thorough review of the literature demonstrates that it is unclear whether open or percutaneous pedicle screw placement results in more facet violations [13][14][15][16]. Moshirfar et al [17] evaluated 204 patients who underwent open screw placement and found that 24% of the cases had cranial facet joint violations.…”
Section: Discussionmentioning
confidence: 99%